Geopolitics of decolonisation: The subaltern diplomacies of Lusophone Africa (1961–1974) - (:unkn) unknown (My University, 2021)
This paper addresses the global engagement of certain African intellectuals who strove for the independence of Lusophone Africa. It does so using geopolitical lenses based on new and multilingual archives. Extending current scholarship on subaltern geopolitics, cultures of decolonisation, and critical development studies, I show the performance of the subaltern diplomacies deployed by political leaders such as Amílcar Cabral, Mário Pinto de Andrade, Agostinho Neto, Eduardo Mondlane, and Marcelino dos Santos in capturing international sympathy for their cause from other scholars, activists, and politicians at different levels (from grassroots movements to state leaders and international organisations) across the divides between Cold War blocs and the fields of the 'First', 'Second', and 'Third World'. I argue that these endeavours disrupted mainstream narratives of development and Euro-centred ideas of assimilation, partly due to their emphasis on education and the production of subaltern histories and geographies that were instrumental to the national construction of new decolonised countries from so-called 'Portuguese Africa'. In the 1960s and early 1970s, these intellectuals used the weapons of culture, public communication, and transnational networking as devices that were as important as the accomplishments of their fellow guerrilla fighters in the battlefield. Additionally, these stories confirm the importance of the archive for tracing cosmopolite, multilingual, and diasporic networks and their spatiality, as well as for doing critical geopolitics from perspectives other than Anglo-or Western-centred ones, thus decolonising geography.
Keywords: African Research